THE SACRED MEANING OF FORESTS IN A COMMUNITY-BASED ECOTHEOLOGICAL PERSPECTIVE: A QUALITATIVE STUDY IN TELUK KEPAYANG VILLAGE, SOUTH KALIMANTAN - Bonifasius; Rinie (STT Bethel Indonesia Jakarta, 2026)
Forest conservation has become an increasingly urgent ecological concern and is often discussed within normative theological frameworks. However, limited research has examined how forest communities interpret and relate to the forest. This article analyzes how forest communities construct meanings and relational practices toward the forest within a community-based ecotheological framework. This study employs a qualitative approach using semi-structured interviews, observation, and document analysis among members of the forest community in Teluk Kepayang Village, South Kalimantan. Data were analyzed thematically through data condensation, categorization, and interpretation. The findings indicate that forest communities perceive the forest as a living space, a source of livelihood, and a sacred space. This collective ecological awareness aligns with creation theology and integral ecology, emphasizing the interconnectedness between humans and creation. However, this awareness is in tension with economic pressures and weak institutional support, preventing it from developing into stable and sustainable collective practices. Conceptually, this article expands community-based ecotheology by arguing that the formation of ecological subjects depends not only on faith-based awareness but also on strengthened social and economic structures, sustained community accompaniment, and cross-sector collaboration. This study contributes to contextual Catholic ecotheology in Indonesia by engaging in dialogical exchange with the lived realities of forest communities.